Organizational Barriers to Oral Health Conversations Between Health Visitors and Parents of Children Aged 9–12 Months Old - Eskytė, Ieva; Gray-Burrows, Kara A.; Owen, Jenny; Sykes-Muskett, Bianca; Pavitt, Sue H.; West, Robert; Marshman, Zoe; Day, Peter F. (Frontiers in Public Health, 2021)
Background. Dental caries is the most prevalent preventable childhood disease and a major public health priority. Local authorities in England have a statutory responsibility to improve child health, including oral health, through the ‘Healthy Child Programme’. The ‘Healthy Child Programme’, which includes the provision of oral health advice is delivered by health visitors to parents of young children. To date, research has mainly concentrated on individual interactions between health visitors and parents, with less attention given to the broader context in which these oral health conversations between health visitor and parents take place. Objective. Our study explored the organisational factors that obstruct health visitors from engaging in meaningful conversations with parents about young children’s oral health. Methods. Qualitative interviews and focus groups were held with health visiting teams (n=18) conducting home visits with parents of 9-12-month olds in a deprived, urban area in the UK. Results. The study revealed the wide variation in what and how oral health advice is delivered to parents at home visits. Several barriers were identified and grouped into four key themes: (1) Priority of topics discussed in the home visits; (2) Finance cuts and limited resources; (3) Oral health knowledge and skills; and (4) Collaborative working with other professionals. It was evident that organisational factors in current public health policy and service provision play an important role in shaping oral health practices and opportunities for behaviour change. Conclusion. Organisational practices and procedures play an important role in creating interaction patterns between health visiting teams and parents of young children. They often limit effective engagement with and positive change in oral health. For future oral health interventions to be effective, awareness of these barriers is essential alongside them being founded on evidence-based advice and underpinned by appropriate theory.